Risk factors for obesity in 6 to 12-year-old children - Andy Japutra; Eddy Fadlyana; Anggraini Alam (Paediatrica Indonesiana, 2015)
Background The causes of obesity in children are multifactorial, including genetics, physiology, metabolism, psychology, socioeconomic status, lifestyle, and culture. Objective To assess for relationships between obesity in 6 to 12-year-old children and maternal nutritional status, maternal education, eating breakfast, eating fast food, physical activity, TV watching, and playing video games. Methods This case-control study included students of Sejahtera Public School aged 6 to 12 years. Questionnaires were distributed to their parents for data on maternal education, eating breakfast, eating fast food, physical activity, TV watching and playing video games. Maternal nutritional status was assessed by one of the researchers. Univariate analysis with Chi–square test was used to assess every risk factor. Those with a P value of <0.25 were subjected to multivariate analysis, performed using multiple logistic regression analysis. Results From June to July 2013, 60 obese children and 60 wellnourished children, as a control group, were enrolled in the study. Obese mothers tended to have obese children [odds ratio/OR 252.48; 95%CI 33.4 to 1908.4]. Children who ate fast food 6–8 times/week, had low physical activity, and watched TV more than 8 hours/week had significantly higher risk for obesity [OR 12.94, 95%CI 1.7 to 100.7; and OR 266.94, 95% CI 7.8 to 9137.7; OR 21.44, 95%CI 2.68 to 171.61; respectively]. Maternal education, eating breakfast, and playing video games were not significant risk factors for childhood obesity. Conclusion Maternal obesity, eating fast food 6-8 times per week, low physical activity and watching TV more than 8 hours/ week are risk factors for childhood obesity.